Romeo and Juliet : Shakespeare's text on the left; modern rendering on the right - Shakespeare, William, 1564-1616. (Clayton, DE : Prestwick House, Inc., 2010)
Two lovers are destroyed by the hatred of their families for one another.
Young Adult
Young Adult.
NP
Keywords: Romeo (Fictitious character) -- Drama; Juliet (Fictitious character) -- Drama; Vendetta -- Italy -- Verona -- Drama; Man-woman relationships -- Drama; Youth -- Italy -- Verona -- Drama; Love -- Drama; Romeo (Fictional character) -- Drama; Juliet (Fictional character) -- Drama; Vendetta -- Drama; Man-woman relationship -- Drama; Youth -- Verona (Italy) -- Drama; Love -- Drama; English drama; Tragedies; Tragedies